1988
DOI: 10.1007/bf00195367
|View full text |Cite
|
Sign up to set email alerts
|

Phase II trials of 5-day vinblastine infusion (NSC 49842), L-alanosine (NSC 153353), acivicin (NSC 163501), and aminothiadiazole (NSC 4728) in patients with recurrent or metastatic renal cell carcinoma

Abstract: One hundred and forty-four evaluable patients with recurrent or metastatic renal cell carcinoma (RCC) were treated with vinblastine infusion (n = 35), L-alanosine (n = 36), acivicin (n = 27), or aminothiadiazole (n = 46). Observed objective response rates of 9%, 3%, 4%, and 2%, respectively indicate that noe of these agents has significant antineoplastic activity in recurrent or metastatic RCC. Multivariate analysis of survival data suggests that initial performance status, time from initial diagnosis to study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(22 citation statements)
references
References 14 publications
0
22
0
Order By: Relevance
“…The maximum-tolerated dose (MTD) identified for infusional vinblastine in combination with oral valspodar was 0.6 mg/m 2 /d for 5 days, for a total dose of 3 mg/m 2 /cycle. This is approximately one-third of the 8.5 mg/m 2 /cycle (1.7 mg/m 2 /d for 5 days) vinblastine dose that can be administered to patients receiving infusional vinblastine for 5 days without a Pgp antagonist (14).…”
Section: Introductionmentioning
confidence: 99%
“…The maximum-tolerated dose (MTD) identified for infusional vinblastine in combination with oral valspodar was 0.6 mg/m 2 /d for 5 days, for a total dose of 3 mg/m 2 /cycle. This is approximately one-third of the 8.5 mg/m 2 /cycle (1.7 mg/m 2 /d for 5 days) vinblastine dose that can be administered to patients receiving infusional vinblastine for 5 days without a Pgp antagonist (14).…”
Section: Introductionmentioning
confidence: 99%
“…It inhibits the growth of human pancreatic carcinoma cell line (MIA PaCa-2) and in vivo the growth of human breast and lung tumor xenografts in athymic mice. In phase I and II trials, acivicin has shown some benefits in the treatment of several solid tumor types (2,6).…”
mentioning
confidence: 99%
“…Other alkylating agents evaluated during the past 6 years in cluded a derivative of razoxane (ICRF-187; 135758), diaziquone (AZQ; 182986), dibromodulcitol or mitolactol (DBD; 04800), carboplatin (CBDCA; 241240), a tri epoxide alkalating agent 1,2,4-triglycidylurazol (TGU; 332488), and a new nitrosourea, a chlorethyl piperidyl derivative (PCNU; 95466). PCNU, 75-100 mg/m2 Q6W induced 1 remission in 79 patients [36,46] A glutamine antagonist from Streptomyces sviceus, acivicin (AT-125; 163501), was administered by contin uous intravenous infusion in a dose of 20 mg/m2/day for 3 consecutive days Q3W [5], The response rate was 4% in 27 cases. Another antitumor antibiotic from Strepto myces alanosinicus, alanosine (L-ALANO; 153353), was given to 36 patients in a dose of 160 mg/m2/day Q4W with 3% responding [5].…”
Section: Standard Cytotoxic Agentsmentioning
confidence: 99%
“…PCNU, 75-100 mg/m2 Q6W induced 1 remission in 79 patients [36,46] A glutamine antagonist from Streptomyces sviceus, acivicin (AT-125; 163501), was administered by contin uous intravenous infusion in a dose of 20 mg/m2/day for 3 consecutive days Q3W [5], The response rate was 4% in 27 cases. Another antitumor antibiotic from Strepto myces alanosinicus, alanosine (L-ALANO; 153353), was given to 36 patients in a dose of 160 mg/m2/day Q4W with 3% responding [5].…”
Section: Standard Cytotoxic Agentsmentioning
confidence: 99%
See 1 more Smart Citation